The Role of Safety Behaviors in the Pathogensis of Contamination Fear: An Experimental Investigation. - Tamer I. FAWZY (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Within the anxiety disorders, behaviors performed in order to mitigate a perceived catastrophic outcome (e.g., washing hands excessively to prevent contamination) are considered safety behaviors. Traditionally, safety behaviors are thought to maintain pathological anxiety by interfering with threat disconfirmation of inaccurate threat estimations. Building on the work of Deacon and Maack (2008) the present study sought to examine how safety behaviors might also contribute to the development and exacerbation of anxiety concerns. This hypothesis was examined in a sample of 61 undergraduate participants. Participants were instructed to either perform a variety of contamination-related safety behaviors, (n = 31) or to simply monitor their cleanliness-related safety behaviors (n = 30) for a week. Results showed that instructions to engage in safety behaviors resulted in statistically significant increases on a measure of contamination fear, threat estimation, and responses on a behavioral-approach task (BAT). The magnitude of this increase was independent of baseline level of contamination fear and did not affect measures of anxiety or depression. The implication of these findings in terms of the effects of safety behaviors on threat estimation, contamination concerns, and attentional processes are discussed. [JCBPR 2015; 4(2.000): 85-96]